Um só destino! Exame histórico sobre o pensamento educacional e político de Marcus Garvey (1887-1940) - Gomes, Fábio Florenço (2020)
This is a research paper on the intellectual thinking of Marcus Garvey (1887-1940), a Jamaican-born journalist, speaker, entrepreneur and social-community organizer. In 1914, Marcus Garvey created the Universal Association for the Progress of the Black (UNIA), an entity that reached thousands of people on the African continent and its diaspora, including Brazil. One of the reasons that made UNIA's expansion possible was its printed communication vehicle, the newspaper The Negro World. The UNIA and The Negro World were two anti-colonial political forces that dominated the period of the 920s-1930s. Throughout the second half of the 20th century, Marcus Garvey's philosophy and opinions influenced both social justice movements in the diaspora and national liberation movements on the African continent. Especially between the years 1980-2000, Marcus Garvey was the thematic reference for the creation of a Pan-African University in Uganda, a Chair in Studies in Jamaica, a community settlement in South Africa and dozens of books published in the Caribbean-England axis. Marcus Garvey and his intellectual thinking represent a transcontinentally shared heritage. Our thesis is that the UNIA, the Rastafarian Movement and the idea of an African Renaissance maintained the cultural vitality of Marcus Garvey in the last 100 years of history (1914-2014). The problem that the research identified was the lack of documents about Marcus Garvey and its historical context in Portuguese in Brazil. The main objective of this research was to elaborate an introductory material to Marcus Garvey, based on a historical examination of education and politics in his intellectual thought.Considering the lack of literature on Marcus Garvey in Brazil, the main question of this investigation was to understand the context of the first visit by a member of the Garvey family to the country in 2013, as part of the global preparations for the celebrations of the 100th anniversary of the founding of UNIA in 2014. The transcribed investigation connects biographical, historical, historiographical studies and information collected from interviews. The innovative theorizing works in dialogue with the Pan-African methodology of Bangura (2011); the historiography of Marcus Garvey by Martin (1983-1986) and Lewis (1986-1988); the UNIA documentation files organized by Hill (1983, 1985); the historical epochs of the Rastafarian movement presented by Barnett (2014), Campbell (1987) and Bonacci (2010); and with the theories on African Renaissance in Diop (1990), Gnonsea (2003) and Obenga (2013).